E-Inclusion in the European Union: Policy Evolution and the Challenges of Digital Transformation - Hristova, Marieta (Research Papers, 2025)
The text examines the development of e-inclusion policies in the context of the digital transformation in the European Union (EU) over the past three decades. E-inclusion is viewed as a key tool for bridging the digital divide and achieving socio-economic inclusion through universal access to information and communication technologies (ICT), promoting digital literacy and the use of emerging technologies. The analysis is based on key strategic documents that highlight the main objectives – overcoming regional and social inequalities in access to ICT, digitising public services, developing digital skills and fostering innovation in sectors such as e-governnance, e-health and e-learning. The text notes that while early strategies focused on infrastructure and internet access, later documents address more complex aspects of the digital divide, including skills, trust and usability. New technologies such as artificial intelligence, quantum computing and cybersecurity offer significant growth potential, but at the same time require ethical and sustainable approaches.The conclusion underlines that despite progress, challenges to e-inclusion remain significant, including social and regional inequalities, the high cost of technology and the need to adapt skills to new technologies.